The Prevalence of Enterotoxin SEA and SEB genes in Staphylococcus aureus Multidrug-resistant Isolates from Clinical Specimens in Baghdad Province - Hussein, Ghufran Hamdan; Mohammed , Rana Kadhum (Iraqi Journal of Science, 2024)
Infections caused by Staphylococcus aureus are frequent in both public and medical settings. The objective of the current study was to assess the prevalence of the SEA and SEB genes in S. aureus clinical isolates. A hundred-sixty samples were obtained from several sources including wounds, urine samples, burns and respiratory tract, during period between October 2022 - January 2023, from Kadhimiya Hospital, Karkh General Hospital and Yarmouk Hospital. The samples were then subjected to several examinations including microscopic examination (gram staining), cultural characteristics on mannitol salt agar, hemolysis characteristic on blood agar and biochemical tests (oxidase, catalase, and coagulase), to confirm S. aureus isolates. These isolates were also subjected to several antibiotics to select the multi-drug resistant (MDR) isolates. Based on the results, high percentages of S. aureus isolates were found to be sensitive to antibiotics, All the isolates (100%) were sensitive to vancomycin (VA), 95.5% were sensitive to both chloramphenicol (C) and rifampin (RA), 93.2% were sensitive to clindamycin (DA), trimethoprim (TR), levofloxacin (LE), followed by 90.9, 88.6 and 75% were sensitive to oxacillin (OX), gentamicin (CN) and doxycycline (DO) respectively. However, 47.75 and 38.6% of isolates were resistant to azithromycin (AZM) and cefoxitin (CX) respectively. The frequency of SEA and SEB genes was estimated by polymerase chain reaction (PCR). The results revealed that, out of 27 S. aureus isolates tested, 8 had a single band for the SEA gene (102 bp), while 9 had a band for the SEB gene (164 bp). The findings indicated that the majority of S. aureus harboured both Sea and Seb genes.